The history of courts and procedure in medieval Canon law - Hartmann, Wilfried; Pennington, Kenneth (History of medieval canon law, 2016)
Introduction to the courts / Kenneth Pennington -- The siting of law between sacred and profane in medieval Italy and Germany / Barbara Deimling -- The practice of Canon law / James A. Brundage -- Procedure in the courts of the IUS commune / Charles Donahue, Jr -- The jurisprudence of procedure / Kenneth Pennington -- The Roman curia / Brigide Schwarz -- Judges delegate / Charles Duggan -- The ecclesiastical courts : introduction / Charles Donahue -- France and adjoining areas / Charles Donahue and Sara McDougall -- Local ecclesiastical courts in England / R.H. Helmholz -- Ecclesiastical procedure in medieval Spain / Antonio Garcia y Garcia -- Ecclesiastical procedure in Eastern Central Europe / Peter Cardinal Erd?